Corporate governance and international bond issues by Latin American corporations - Georgina Núñez Reyes; Ignacio Perrotini Hernández; Francisco López-Herrera (CEPAL Review, 2018)
This paper analyses the relationship between corporate bond issues and the existence of corporate governance frameworks that influence the development of financial markets by reducing information asymmetries and conflicts of interest. To this end, the international corporate bond market is reviewed and corporate governance standards in Brazil and in the four countries belonging to the Latin American Integrated Market (MILA) —Chile, Colombia, Mexico and Peru— are evaluated using a bond issues indicator developed by the Economic Commission for Latin America and the Caribbean (ECLAC), the Andean Development Corporation (CAF) and the Inter-American Development Bank (IDB). The evidence gathered using a probit panel model and a pooled probit model indicates that adherence to corporate governance standards can increase the likelihood that a firm will be able to carry out a successful international bond issue.